The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.31265/usps.35
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Organizational Change in Hospitals: Exploring how hospital leaders and employees can contribute to successful outcomes

Abstract: Over the past four decades, a large number of public health care reforms and policies internationally and nationally have been aimed at solving these challenges. At the outset of 2018, the Norwegian Minister of Health Services restated that reduction in waiting times and quality improvement are strategic goals for the Norwegian hospital sector. The policy vision is to create "The Patients' Health Service". He pointed to the development of new ways of planning and organizing services as means to reach those goa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 162 publications
0
3
0
Order By: Relevance
“…Challenges in terms of managing vertical alignment are frequently demonstrated in healthcare organisations, e.g., [21,22]. Key reasons for poor vertical alignment have been related to conficting institutional logics in development work in healthcare [23] and in public eldercare [24]. Specifcally, challenges regarding vertical alignment in public eldercare are seen in, for example, failed broader implementations of welfare technology due to a lack of resources, know-how, and follow-up in the implementation process [19,25].…”
Section: Introductionmentioning
confidence: 99%
“…Challenges in terms of managing vertical alignment are frequently demonstrated in healthcare organisations, e.g., [21,22]. Key reasons for poor vertical alignment have been related to conficting institutional logics in development work in healthcare [23] and in public eldercare [24]. Specifcally, challenges regarding vertical alignment in public eldercare are seen in, for example, failed broader implementations of welfare technology due to a lack of resources, know-how, and follow-up in the implementation process [19,25].…”
Section: Introductionmentioning
confidence: 99%
“…These logics are embedded in the organization and thus regulate managers' and employees' behavior and affect organizations' opportunities for improvement work (Thornton et al, 2012; Thornton & Ocasio, 2008). The notion of institutional logics has often been used to grasp and illustrate how different logics and values interact across macro‐ and micro levels in, for example, organizational improvement work (Øygarden, 2020; Reay & Hinings, 2005). One type of institutional logic is related to values of the state and focuses on common goods and public authorization (Thornton et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier research on the relation between different institutional logics has demonstrated that conflicting logics can coexist, interact supportively or clash (Reay & Hinings, 2005). Research on institutional logics in health and social care has often focused on the conflicts between professional, state and managerial corporate logics (Andreasson, 2018) and suggests that such conflicts constitute important obstacles to successful improvement work (Andreasson et al, 2016; Dellve & Wikström, 2009; Øygarden, 2020). However, to our knowledge, no previous studies have focused on the alignments between, on the one hand, organizational gender equality and, on the other, institutional logics that relate to state and professional values.…”
Section: Introductionmentioning
confidence: 99%